Risk Assessment Algorithms in Pharmacovigilance: A Review - T. M. Bukatina (Безопасность и риск фармакотерапии, 2025)
INTRODUCTION. In the Russian Federation, risk-based approaches/methods to assess the safety of medicinal products have been used since 2016, but existing models based on them are few and applicable mainly to healthcare organizations. This underscores the need to systematise risk assessment procedures for medicinal products within pharmacovigilance frameworks by pharmacovigilance specialists using a risk-based approach in the risk management system.AIM. This study aimed to analise of the key tools of the risk-based approach and optimise their application in medicinal product risk management systems.RESULTS. A four-stage risk management framework for medicinal products was developed using a risk-based methodology: identification of risks associated with medicinal product use, determination of risk factors specific to individual medicinal products, correlation and evaluation of data for each risk factor with each of the identified risks and a conclusion on the benefit-risk ratio of medicinal products use. Key tools for implementing this approach include: 1) organization of work with information about adverse drug reactions; 2) active monitoring of drug safety; 3) development, implementation, and evaluation of risk mitigation measures; 4) targeted communication of safety issues to healthcare professionals, patients, and caregivers. Spontaneous reports, reports of adverse drug reactions received on request from the holder of the registration certificate, data from pharmacoepidemiological studies, information published in the scientific medical literature, as well as Internet resources are used as sources of information to identify the risks of adverse drug reactions at the post-registration stage of medicinal products circulation. Risk factors for the development of adverse drug reactions in the use of medicinal products are physiological changes in the patient's body, gender, age, presence of comorbidities, genetic predisposition, differences in pharmacokinetics and pharmacodynamics of medicinal products depending on the patient's age, use of off-label medicinal products. A five-step algorithm for medicinal product risk assessment was developed: parameters and objectives of risk evaluation, data sources, potential risks, severity and probability of risks, and benefit-risk ratio assessment. Additional risk minimisation measures are summarised.CONCLUSIONS. The proposed variant of the risk-based approach using available tools can be used by pharmacovigilance specialists in drug risk management.